Impact of Biodiversity on International Tourism: A Cross Country Analysis - Karki Nepal, Apsara; Nepal, Mani (Economic Journal of Nepal, 2012)
Using cross country data from 134 countries around the world, this research investigates the impact of biodiversity on tourist arrivals and earnings from the international tourism. Our results indicate that the biodiversity index is a significant determinant of the international tourist arrivals and earnings from international tourism. The access to the Internet is equally important for attracting international tourists in a country. These results remain robust when we include lagged value of biodiversity index. The Economic Journal of Nepal, Vol. 35, No. 1, January-March 2012 (Issue N0. 137)